The use of gliricidia sepium in the supplementary feeding of crossbred female calves - González Villalobos, D.; Palomares Naveda, R.; Navarro, E.; Razz, Rosa; Soto Castillo, G.; Quintero Moreno, A. (Revista Científica de la Facultad de Ciencias Veterinarias, 1970)
To evaluate the effect of supplementation in female calves with flour of Gliricidia sepium leaves (GS) on partial and final body weight (BW) and average daily gain (ADG) a study was undertaken in the “San Pedro Farm” located in Zulia State, in a tropical sub-humid forest environment of Venezuela. The data were analyzed by the least-square analysis of variance-covariance of The Statistical Analysis System, testing effects of treatment on 7 weaned Holstein crossbred female calves, 5 months old at initiation, and supplemented with a growing ration (2% of body weight): (a) supplementation with 100% of feed concentrate (TA) and (b) a mixture of 60% corn meal + 40% of dehydrated GS flour + 50 g./animal/day of complete mineral mixture (TR). The female calves supplemented with TA reached a higher BW (106.65 Ó 2.51 kg.) and ADG (334.61 Ó 42 g/d) than the female calves fed with TR (BW=96.06 Ó 2.51 kg, ADG=157 Ó 42 g/d). The apparent cause for these results was the cutting age (5 months old) of the plant used to make the ration and the lower feed intake in TR. It is important to cut the GS plant green and very young (between 6 and 12 weeks old) because it has the best rate of digestibility at this stage. It is suggested prepare a ration with a minor proportion (30%) of GS flour, adding edible molasses to improve the palatability.